Efficacy and Safety of Transarterial Chemoembolization in Elderly Patients of Advanced Hepatocellular Carcinoma With Portal Vein Tumor Thrombus: A Retrospective Study - Tang, Qinghe; Huang, Wei; Liang, Jun; Xue, Junli (Frontiers in Oncology, 2021)
Objective: The retrospective study aimed to evaluate the safety and efficacy of transcatheter arterial chemoembolization (TACE) in elderly patients diagnosed as hepatocellular carcinoma (HCC) accompanied with portal vein tumor thrombosis (PVTT). Methods: HCC patients aged 70-year-old and above from January 2015 to December 2019 were included. Efficacy data including OS, PFS, DCR, and ORR and safety data were collected. Outcomes of HCC patients in underwent TACE were compared with those patients underwent best supportive care (BSC). Subgroup analyses were also conducted in the patients with different types of PVTT. Results: Among 245 elderly HCC patients, 124 were enrolled. Out of these, 62 underwent BSC while 62 underwent TACE. No major differences in the baseline characteristics of the two groups. TACE was associated with better median OS compared with BSC (11.3m vs. 7.8m; P<0.001). Subgroup analyses showed that patients with type I and II PVTT could benefit from TACE compared with BSC, based on that OS was 14.3m vs. 7.8m (P=0.007) and 13.0m vs. 8.0m (P=0.002), respectively. The DCR in the TACE group was 62.9%, and 17.7% in the BSC group (p<0.001). The ORR in TACE group was 35.5%, while 0.0% in BSC group (p<0.001). Multivariable analyses showed that patients undergoing TACE had 52.0% lower odds of mortality compared with patients undergoing BSC (HR: 0.48; 95%CI: 0.32-0.72). The media PFS was improved following TACE treatment (7.5m vs. 4.0m; P<0.001). TACE could significantly prolong the PFS in both type I and II PVTT subgroups, without significant improvement in type III PVTT patients (4.5m vs. 2.7m; P=0.103). Type III PVTT patients in the TACE group had more AEs than type I and type II PVTT patients. According to multivariable analyses, PVTT types (type III vs. type I-II) (HR: 2.18; 95%CI: 1.29-3.70; P=0.004), tumor diameter (>5 cm vs. ≤5 cm) (HR: 1.94; 95%CI: 1.28-2.93; P=0.002), and treatment (TACE vs. BSC) (HR: 0.48; 95%CI: 0.32-0.72; P<0.001) were independent indicators of overall survival. Conclusions: In elderly advanced HCC patients with PVTT, palliative TACE treatment can be an accessible effective measure to improve the OS and PFS for both type I and type II PVTT patients.